Patient‐Reported Outcomes in Oncology Clinical Trials: Stakeholder Perspectives from the Accelerating Anticancer Agent Development and Validation Workshop 2019. (9th June 2020) - Bhatnagar, Vishal; Hudgens, Stacie; Piault‐Louis, Elisabeth; Jones, Lee; Beaver, Julia A.; Lyerly, H. Kim; Reaman, Gregory; Fleming, Thomas; Kluetz, Paul G.
Abstract : The measurement and analysis of patient‐reported outcomes is important in cancer clinical trials. This commentary reports advances and challenges from presentations at the 2019 Accelerating Anticancer Agent Development and Validation (AAADV) Workshop Patient‐Reported Outcomes Session.